The heritages of Palembang Sultanate in Palembang City / Farida - Farida (2012)
This writing is aimed to present some historical places related to the Sultanate of Palembang Darussalam (17th - 19th centuries). From the result of examination it showed that as the first and the last sultanate in Palembang (South Sumatera Province now), the sultanate inherited some historical sites and buildings to be maintained and preserved. In fact, the advanced technology and modern era have made these important heritages seemed to be ignored. In addition, the government apparatus, the leader of society, and the communities in general did not give their much concern to the further maintenance and preservation of these valuable heritages. It is important to concern with the historical sites and buildings in order that these heritages will be long lasting survived and useful for the interest of preservation of the historical values. The inherited historical sites and buildings of Palembang Sultanate are Agung Mosque, Kuto Besak Palace, Tengkurep Cauldron, the Graveyard Complex of Sabo Kingking and Geding Suro, Kemaro/Gombora Island, Siguntang Hill, Komering River Mouth (Plaju), Bagus Kuning, areas of 16-28/29 Ilir. Those sites have important historical values. It is probable that these sites can be one of the World Heritage sites, since these heritages become precious resources of information and real proofs describing the past condition in Palembang. Not only do the heritages describe Palembang as a central of trading and religiousness from the period of Sriwijaya sovereignty until the period of Palembang Sultanate, but also the evidence the persevering struggle of Palembang against the Dutch and British colonials who wished to have control over Palembang for its strategic location and its natural resource of tin.